Analisis Mendalam Tingkat Literasi Pajak Masyarakat Indonesia di Era Transformasi Digital: Evaluasi Kepatuhan dan Kepercayaan Publik (Tahun 2025) - Anggi Zihni Listiani (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to measure and analyze the level of tax literacy among Indonesian society in 2025, amidst the acceleration of digital transformation in the public sector and changes in taxpayer demographics. Using a mixed-methods approach with a sequential explanatory design, this study combines a quantitative survey of 5,000 respondents across 34 provinces and in-depth qualitative interviews. The results indicate that the National Tax Literacy Index (NTLI) stood at 62.4% in 2025. This figure reflects a phenomenon of "mechanical compliance," characterized by high administrative capability but moderate essential awareness. This study specifically highlights that innovations in public digital communication platforms, adaptive message delivery strategies, and public understanding of asset reporting transparency and state financial management are the most determinant variables in promoting voluntary tax compliance. These findings are expected to serve as a foundation for formulating more inclusive, behaviorally-based fiscal policies.